Oiseaux de proie diurnes - Jean Lapointe; Marc J. Mazerolle; Louis Imbeau; Junior A. Tremblay; Charles Maisonneuve (Le Naturaliste canadien, 2014)
The province of Québec has considerable potential for the continued expansion of its wind power industry. Wind farms may be a cause of mortality for birds of prey and could have a particularly negative affect on certain vulnerable species, such as the peregrine falcon. To help determine the types of sites to favour for the establishment of new wind farms, we compared the use of 5 environments by 10 female peregrine falcons nesting in southern Québec during the period from 2008 to 2010. To minimize potential collision risks with wind turbines, the environments least used by females peregrine falcons should be preferentially chosen for locating wind farms. Once the young had fledged, females traveled farther afield than when the chicks were flightless. During this period, 90 % of the telemetry locations in corn and soybean fields were recorded within an 8.3-km radius of the nest, compared to a 15.9-km radius for other crops. Also, females were less likely to use corn and soybean fields, than other crops and environments that were not suitable for hunting. Our results lead to recommendations regarding the environments to favour for the location of future wind farms, and the minimal distances that should be respected between wind farms and peregrine falcon nests sites to minimize collision risks. Le Québec offre un potentiel considérable pour le développement de l’industrie éolienne. Cette industrie peut être à l’origine de mortalités chez les rapaces et pourrait affecter certaines espèces vulnérables comme le faucon pèlerin. De 2008 à 2010, nous avons comparé l’utilisation de 5 types de milieux par 10 femelles nicheuses de faucon pèlerin dans le Québec méridional, afin de déterminer ceux à favoriser pour l’implantation de parcs éoliens. Les milieux les moins utilisés par les femelles étaient ceux considérés comme diminuant les risques de collision avec les éoliennes. Après l’envol des fauconneaux, les femelles parcouraient de plus grandes distances que lorsque les fauconneaux étaient confinés au nid. À cette ...